THE INFLUENCE OF ADVERTISING, BRAND IMAGE, AND PRICE ON CONSUMER LOYALTY OF HM SAMPOERNA CIGARETTES IN THE PEOPLE OF LHOKSEUMAWE - Muhammad Yani Fadhil; Halida Bahri; Rusydi Abubakar; Muchsin (RADJA PUBLIKA, 2025)
This research aims to determine the influence of advertising, brand image and price on consumer loyalty for HM Sampoerna cigarettes in the people of Lhokseumawe City. The research method used is a quantitative method with a survey approach. This research was conducted on all consumers who consumed HM Sampoerna cigarettes in the city of Lhokseumawe, totaling 100 consumers. The data used in this research is primary data obtained by distributing questionnaires directly to 100 respondents. The data analysis technique used is multiple linear regression analysis using the Statistical Program for Product and Service Solution (SPSS) software. Where all these variables will be used using a Likert scale. The research results show that advertising, brand image and price together have a positive and significant effect on consumer loyalty for HM Sampoerna cigarettes. With an advertising regression value of 0.728 and a significant value of 0.000. This shows that advertising has a positive and significant effect on consumer loyalty, so the more attractive and effective the advertising for HM Sampoerna cigarettes, the higher the consumer loyalty to the brand. Brand image has a regression value of 0.269 with a significance value of 0.041. This shows that brand image has a positive and significant effect on consumer loyalty, so a good brand image can increase consumer loyalty. Price has a regression value of 0.478 with a significance value of 0.000. This shows that price has a positive and significant effect on consumer loyalty, so the price given by HM Sampoerna is in accordance with the product quality that consumers receive, which can increase consumer loyalty.